Analysis of Rice Price Trend and Vertical Integration of Rice Market in Indonesia - Asih Kusumaningsih; Jamhari Jamhari; Dwidjono Hadi Darwanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
The aims of this study were (1) to determine the trend of retail rice price in Indonesia and the price of grain at the farmer level in Indonesia and (2) to identify the vertical integration of the rice market in Indonesia. The monthly data of retail rice price and the price of grain at the farmer level (price of harvested dried grain at the farmer level) in Indonesia during January 2008 - January 2016 were used in this study. The least squares method was applied to determine the trend of prices, while Co-integration Model of Engle-Granger and ECM was used to estimate the vertical integration of Indonesian rice market. The results indicated that both types of prices had an upward trend. In the analysis of the vertical integration of rice market in Indonesia, there was a long-term balance relationship and short-term equilibrium relationship.